Different effect of NiMnCo or FeNiCo on the growth of type-Ⅱa large diamonds with Ti/Cu as nitrogen getter - 李尚升 张贺 宿太超 胡强 胡美华 龚春生 马红安 贾晓鹏 李勇 肖宏宇 (Chinese physics B, 2017)
In order to synthesize high-quality type-Ⅱa large diamond, the selection of catalyst is very important, in addition to the nitrogen getter. In this paper, type-IIa large diamonds are grown under high pressure and high temperature（HPHT） by using the temperature gradient method（TGM）, with adopting Ti/Cu as the nitrogen getter in Ni70Mn25Co5（abbreviated as NiMnCo） or Fe（55）Ni（29）Co（16）（abbreviated FeNiCo） catalyst. The values of nitrogen concentration（Nc） in both synthesized high-quality diamonds are less than 1 ppm, when Ti/Cu（1.6 wt%） is added in the FeNiCo or Ti/Cu（1.8 wt%） is added in the NiMnCo. The difference in solubility of nitrogen between both catalysts at HPHT is the basic reason for the different effect of Ti/Cu on eliminating nitrogen. The nitrogen-removal efficiency of Ti/Cu in the NiMnCo catalyst is less than in the FeNiCo catalyst. Additionally, a high-quality type-Ⅱa large diamond size of 5.0 mm is obtained by reducing the growth rate and keeping the nitrogen concentration of the diamond to be less than 1 ppm, when Ti/Cu（1.6 wt%） is added in the FeNiCo catalyst.